Ankle arthroplasty: A review and summary of results from joint registries and recent studies. Issue 6 (28th June 2018) - Syed, Farhan; Ugwuoke, Anthony
Abstract : Total ankle arthroplasty offers a reasonable alternative to ankle arthrodesis in carefully selected patients. It is debatable whether rheumatoid arthritis patients have better outcomes compared with those who have ankle arthroplasty for either primary osteoarthritis or post-traumatic arthritis. Aseptic loosening and infection are the most common complications requiring revision. It is worth noting that some of the best survival rates are seen in the surgeon-designer case series. The uncemented mobile or fixed bearing prostheses have better outcomes compared with their older counterparts. There is no convincing evidence to suggest superiority of one design over another among the currently available prostheses. Ankle arthroplasty surgery has a steep learning curve; the prosthesis choice should be driven by the surgeon's training and experience. Cite this article: EFORT Open Rev 2018;3:391-397. DOI: 10.1302/2058-5241.3.170029